An alternative parameter to characterize biogas materials: Available carbon-nitrogen ratio. (April 2017) - Wang, Ming; Li, Wenzhe; Li, Pengfei; Yan, Shuiping; Zhang, Yanlin
Highlights: AC/N was firstly proposed as an novel parameter to characterize biogas materials. AC/N is better to characterize the organic wastes rich in recalcitrant components. The relationship between AC/N and AD process was investigated. AC/N of 11–15 was found to be optimal for semi-continuous AD process. Abstract: Available carbon-nitrogen ratio (AC/N) was proposed as an alternative parameter for evaluating the potential of biogas materials in this paper. In the calculation of AC/N ratio, only the carbon that could be effectively utilized in anaerobic digestion (AD) process is included. Compared with total C/N, AC/N is particularly more suitable for the characterization of biogas materials rich in recalcitrant components. Nine common biogas materials were selected and a series of semi-continuous tests for up to 110 days were carried out to investigate the source of available carbon and the relationship between AC/N and the stability of AD process. The results showed that only the carbon existing in proteins, sugars, fat and hemicelluose should be considered as available carbon for anaerobic microbes. Besides, the optimal AC/N for semi-continuous AD process was preliminarily determined to be 11–15. Taken together, our results demonstrate that AC/N is more effective than total C/N in the evaluation of the potential performance of AD process.